Increasing Biology Learning Activity Through the Project Based Learning Model with the Culturally Responsive Teaching (CRT) Approach - Dian Rifkanita; Lilies Tangge; Nurhaidah Nurhaidah (Equator Science Journal, 2025)
This study is a Classroom Action Research (CAR) that aims to improve the activeness of Grade X Melati students at SMA Negeri 6 Palu through the implementation of the Project-Based Learning (PjBL) model with a Culturally Responsive Teaching (CRT) approach. The research was conducted in two learning cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were 31 students. The research instruments included student learning activeness observation sheets and a student learning activeness questionnaire. Data analysis was carried out by reflecting on observation results and calculating the scores obtained for each activeness indicator. The findings revealed an increase in student learning activeness from the pre-cycle to Cycle I and Cycle II. In the pre-cycle, the average percentage of activeness was only 51%, which then increased to 66% in Cycle I, categorized as moderately active. In Cycle II, the percentage further increased to 88%, categorized as highly active. These results indicate that the PjBL model integrated with the CRT approach significantly enhanced students’ learning activeness. These findings imply that the integration of the PjBL model with a CRT approach has the potential to be applied beyond specific subjects and across different educational levels, fostering participatory, contextual, and culturally responsive learning.